The Potential Overview of PV System Installation at the Quarry Open Pit Mine PT. Bukit Asam, Tbk Tanjung Enim - Junaedi, Ketut; Dewi, Tresna; Yusi, Muhammad Syahirman (Kinetik: Game Technology, Information System, Computer Network, Computing, Electronics, and Control, 2021)
South Sumatra has an established state-own enterprise exploring the Quarry Open Pit Mine. This mining process leaves some abondance open field that has a high potential to install a PV system. The Government has undertaken an initial analysis of 200 hectares of ex-mining land for this purpose. This paper analyzes the potential for PV panels to be installed at PTBA Tanjung Enim Quarry Open Pit Mine. The location of the PV panel in the open pit Quarry for this analysis is at an altitude of +140 m above sea level. Meanwhile, the PTBA Tanah Putih Township housing site where the PV comparison panel is installed is located on the altitude of +100 m above sea level, and within 2.97 km from the mine. PV panels installed in Open Pit mines generate better electricity and efficiency compared to PV panels installed outside the mine (in PTBA Township Housing). The difference of Isc between PV Panel installed in Quarry Open Pit Mine and Township is 0.0075 A. The Iload measured on the Quarry Open Pit Mine PV panel is 0.5478 A higher than the Township PV panel. Meanwhile, Voc measured on Quarry Open Pit Mine PV panel is smaller than Township PV panel, approximately 0.266 V and Vload of Quarry Open Pit Mine PV panel is 0.266 V larger than Township PV panel. The produced power of Quarry Open Pit Mine PV panel is 11.02 W larger than the Township PV panel. From the total value, the average efficiency produced by Quarry Open Pit Mine PV panels is 2.31 % higher than the efficiency produced by Township PV panels. This research shows the possibility and advantage of installing a PV system on a Quarry Open Pit Mine.